2002
DOI: 10.1038/sj/pcan/4500550
|View full text |Cite
|
Sign up to set email alerts
|

No association of the 5′ promoter region polymorphism of CYP17 gene with prostate cancer risk

Abstract: 4Hemocentro de São José do Rio Preto, Sáo Paulo, Brazil CYP17 gene encodes the enzyme cytochrome p450c17a, which mediates two steps in the steroid biosynthesis pathway. Steroid hormones are believed to play a key role in the etiology of prostate cancer. A polymorphic T?C transition in the 5 0 promoter region of CYP17 creates an additional Sp1-type (CCACC box) promoter site (allele A2). We have evaluated the genotypic and allelic distribution of this polymorphism among 92 prostate cancer patients in order to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…With the subgroup analysis of the various genotype models, ethnicity was a major risk factor for prostate cancer. Several authors have reported the association between CYP17 rs743572 polymorphism and the risk of prostate cancer using African ancestry as a determinant (Lunn et al, 1999; Kittles et al, 2001; Stanford et al, 2002; Cicek et al, 2004; Sarma et al, 2008; Beuten et al, 2009; Dos Santos et al, 2002). This meta-analysis disagrees with a study by Wang et al (2011), who reported no significant association between CYP17 rs743572 polymorphism and prostate cancer in Caucasians and Asians.…”
Section: Discussionmentioning
confidence: 99%
“…With the subgroup analysis of the various genotype models, ethnicity was a major risk factor for prostate cancer. Several authors have reported the association between CYP17 rs743572 polymorphism and the risk of prostate cancer using African ancestry as a determinant (Lunn et al, 1999; Kittles et al, 2001; Stanford et al, 2002; Cicek et al, 2004; Sarma et al, 2008; Beuten et al, 2009; Dos Santos et al, 2002). This meta-analysis disagrees with a study by Wang et al (2011), who reported no significant association between CYP17 rs743572 polymorphism and prostate cancer in Caucasians and Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Seven small studies (including 8 to 132 prostate cancer cases) have explored the relationship between the rs743572 ( CYP17 ) polymorphism and the risk of prostate cancer in populations of African ancestry. Six of these studies were carried out in the US [ 28 33 ], the remaining study being performed in Brazil [ 34 ]. Three meta-analyses based on these studies reported that the C allele or the CC genotype was marginally, but not significantly associated with prostate cancer risk [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%